An experimental study on the effect of prosecutorial Brady violations on confidence in exonerating individuals wrongfully convicted of murder - Navarro, John C.; Hansen, Michael A. (Springer, 2025)
Objectives
While several contributing factors can lead to wrongful convictions, it is unclear whether the public perceives these methods of exonerating convicted murderers differently.
Methods
We distributed an online survey to a nationally representative sample of 1193 individuals. After reading a prompt about the increased attention and production of digital media on wrongful convictions and exonerations, respondents were randomized into two conditions to evaluate their confidence in the exoneration of a convicted murderer across four contributing factors. The experimental condition contained the addition of prosecutorial misconduct in withholding evidence.
Results
Public confidence in wrongful conviction exonerations varied across the four contributing factors, with DNA evidence consistently held in the highest regard. Confidence then followed a descending order, beginning with police-induced forced confessions, false testimonies, and eyewitness statements, with all three showing increased confidence ratings when prosecutorial misconduct was involved.
Conclusions
The public distinguishes between contributing factors in murder exonerations. DNA is the most trusted evidence for murder exonerations regardless of misconduct, while confidence in the other contributing factors to exonerate murderers significantly increases when prosecutorial misconduct is present.